THE IMPACT OF PARENTING STYLES ON THE SOCIOEMOTIONAL DEVELOPMENT OF 5-6 YEAR-OLD CHILDREN INLABULIA VILLAGE, JONGGAT DISTRICT, CENTRAL LOMBOKREGENCY - Safitri, Dewi (Sinar Lima, 2025)
This study aims to determine the impact of parenting styles on the social and emotional development of children aged 5-6 years in RT 15, Labulia Hamlet, Labulia Village, Jonggat District, Central Lombok Regency. This study used a qualitative method, with data sources consisting of parents, children aged 5-6 years, and neighbors. Data collection techniques used in this study included observation, interviews, and documentation. Data analysis was conducted using Miles and Hubermen, with the steps of data reduction, data presentation, and conclusions. The results of the study revealed that parents use different parenting styles for the social and emotional development of children aged 5-6 years. Several parenting styles applied by parents to children aged 5-6 years can impact their social and emotional development. The impact of authoritarian parenting is that children lack self-confidence in their social environment, while the impact of permissive parenting is that children tend to develop uncontrolled behavior so that children find it difficult to obey rules and the impact of democratic parenting is that children act actively in their lives. The conclusion of this study is that parenting styles significantly influence the social and emotional development of children aged 5-6 years.